ANALYSIS OF BUILDING MATERIALS FOR SIMPLE BUILDING FLOOR COVERINGS - Suharry; Nurhasan syah; Makkah HM; Andi Sri Rezky Wulandari (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to analyze the variation of building materials used as floor coverings in simple buildings. Through a quantitative approach, this study examined three types of floor covering materials that are often used: ceramic, vinyl, and cement. The sample was taken from five simple buildings in urban areas and five in rural areas. The variables assessed include cost, durability, comfort, and ease of installation. The data were analyzed using descriptive and inferential statistics to compare the effectiveness of each material. The results showed that ceramics, although more expensive, offered better durability and aesthetics, while vinyl stood out for its comfort and ease of installation. Cement floor coverings, meanwhile, are an economical option but lack in durability and comfort. The study recommends the use of ceramics for high-traffic areas and vinyl for areas that require comfort at a lower cost. This finding is expected to provide guidance for builders and homeowners in choosing floor covering materials that suit their needs and economic conditions.